2017
DOI: 10.1016/j.joep.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in financial risk tolerance

Abstract: The purpose of this research is to explore gender differences in financial risk tolerance using a large, nationally representative dataset, the Survey of Consumer Finances. The impact of the explanatory variables in the model is allowed to differ between men and women to decompose gender differences in financial risk tolerance. The results indicate that gender differences in financial risk tolerance are explained by gender differences in the individual determinants of financial risk tolerance, and that the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(133 citation statements)
references
References 63 publications
7
117
1
8
Order By: Relevance
“…This method can date back to Jackson and Lindley (1989) who examined wage discrimination between men and women. Similar techniques have been used by other studies since then (Fisher & Yao, 2017;Fontes & Kelly, 2013;Gutter, Fox, & Montalto, 1999).…”
Section: Discussionmentioning
confidence: 88%
“…This method can date back to Jackson and Lindley (1989) who examined wage discrimination between men and women. Similar techniques have been used by other studies since then (Fisher & Yao, 2017;Fontes & Kelly, 2013;Gutter, Fox, & Montalto, 1999).…”
Section: Discussionmentioning
confidence: 88%
“…This method can date back to Jackson and Lindley () who examined wage discrimination between men and women. Similar techniques have been used by other studies since then (Fisher & Yao, ; Fontes & Kelly, ; Gutter, Fox, & Montalto, ).…”
Section: Methodsmentioning
confidence: 91%
“…Individuals'degree of financial risk tolerance influences their decisions to include certain assets in their portfolio composition (Hallahanet al, 2004). Furthermore, it is suggested that financial risk tolerance is one of the main factors influencing an individual's decisions for his/herstrategies in attaining their goals, security choices, and asset allocation selections (Fisher & Yao, 2017). Hemrajani and Sharma (2018) suggest that financial risk tolerance differs from one individual to the next based on numerous influential.…”
Section: Introductionmentioning
confidence: 99%